Discrete Optimization Via Marginal Analysis - Fox, Bennett (Management Science, 1966)
Discrete optimization subject to one constraint is attacked by Lagrangian analysis. Incremental allocation schemes are given that generate undominated allocations. In an important special case, the complete family of undominated allocations is generated.